2018
DOI: 10.13080/z-a.2018.105.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coapplication of poultry litter biochar and mineral fertilisers on soil quality and crop yield

Abstract: This study evaluated the effects of poultry litter biochar application on soil quality and yield of pasture grass mixture. A micro-plot field experiment was established on an Eutric Cambisol (CM-eu) with five treatments: 1) soil without fertilisation (control), 2) mineral fertilisation (NPK), 3) NPK + poultry litter at a rate of 5 t ha-1 DM (PL), 4) NPK + poultry litter biochar at a rate of 2.25 t ha-1 DM (PLBI) and 5) NPK + poultry litter biochar at a rate of 5 t ha-1 DM (PLBII). Given the need to create comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Ashes are rich in oxides and hydroxides of alkali metals, which are easily dissolved and react rapidly with the soil, thereby increasing its pH [48]. These results are consistent with Mierzwa-Hersztek et al [49], whose research showed that alkaline substances are easily released from BioC. Their results also showed a positive correlation between pH of the soil and soil's enzymatic activity-BioC might contain labile substrates that enhance the activity of soil microorganisms.…”
Section: Effect Of Bioc Addition On Soil Phsupporting
confidence: 85%
“…Ashes are rich in oxides and hydroxides of alkali metals, which are easily dissolved and react rapidly with the soil, thereby increasing its pH [48]. These results are consistent with Mierzwa-Hersztek et al [49], whose research showed that alkaline substances are easily released from BioC. Their results also showed a positive correlation between pH of the soil and soil's enzymatic activity-BioC might contain labile substrates that enhance the activity of soil microorganisms.…”
Section: Effect Of Bioc Addition On Soil Phsupporting
confidence: 85%
“…Recently, it has been shown that the application of a mixture of mycorrhizal species ( R. intraradices , F. mosseae , Glomus hoi ) and phosphorus fertilizer could improve the EO yield and physiological characteristics of peppermint ( Mentha piperita ) cultivated under different water stress conditions [ 283 ]. On the other hand, several studies have reported beneficial effects after the co-application of mineral and organic fertilizers [ 284 , 285 ]. For example, synergistic effects on fruit quality improvement have been described in the case of co-application of mineral and organic amendments under water deficit in pomegranate [ 286 ].…”
Section: Synergistic Effects Of Amf and Other Amendments On Mapsmentioning
confidence: 99%
“…The size of crops yield is dependent on various factors including soil-climatic conditions and soil management (Kováčik & Ryant, 2019;Aydin et al, 2020). Crops have different requirements on temperature and precipitation; however, their optimal distribution is crucial during the vegetation season of crops (Gantner et al, 2008).…”
Section: Crops Yieldmentioning
confidence: 99%